2007
DOI: 10.1111/j.1745-4573.2007.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fat Level and Storage Time on Lipid and Color Stability of Naturally Fermented Turkish Sausages (Sucuk)

Abstract: Lipid oxidation, lipolysis and color stability of naturally fermented Turkish sausages with different initial fat content (10, 20 and 30%) were studied during 60 days of storage of the vacuum‐packed sausages at 4 ± 2°C. During storage, thiobarbituric acid (TBA) and total free fatty acids (FFAs) were measured to determine lipid oxidation and lipolysis. Changes in color were determined by measuring Commission Internationale de l'Eclairage (CIE) L* (lightness), a* (redness) and b* (yellowness) color variables. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
6
9
0
3
Order By: Relevance
“…This final drop was attributed to the instability of the malonaldehyde (Melgar, Sanchez-Monge, & Bello, 1990). The highest lipid oxidation values were also detected in HF sausages by Olivares et al (2011), Soyer andErtas (2007) and Liaros et al (2009). Our final values were the same order of those reported by other authors Soyer et al, 2005), who found values below 1.5.…”
Section: Lipolysis and Lipid Oxidationsupporting
confidence: 89%
See 1 more Smart Citation
“…This final drop was attributed to the instability of the malonaldehyde (Melgar, Sanchez-Monge, & Bello, 1990). The highest lipid oxidation values were also detected in HF sausages by Olivares et al (2011), Soyer andErtas (2007) and Liaros et al (2009). Our final values were the same order of those reported by other authors Soyer et al, 2005), who found values below 1.5.…”
Section: Lipolysis and Lipid Oxidationsupporting
confidence: 89%
“…TBARS values increased significantly (Pb0.001) during process from (0.38, 0.43 and 0.44 to 0.98, 1.40 and 1.66 mg MDA/kg of sausage Pb0.01 for LF, MF and HF groups, respectively) at 28 days of ripening process. The increase in TBARS index during ripening stage was also reported by the other authors (Liaros et al, 2009;Olivares et al, 2011;Soyer & Ertas, 2007) in fermented sausages. From these maximum values, a significant (Pb0.001) drop was observed at the end of process reaching final average values of 0.92, 1.06 and Table 3 Evolution of free amino acids (FAA) concentrations (mg/100 g DM) during ripening of dry-cured foal sausages with different fat contents (mean±standard deviation of three samples).…”
Section: Lipolysis and Lipid Oxidationsupporting
confidence: 75%
“…However, no significant differences in lightness and yellowness were observed during the storage period. According to Soyer and Ertas (2007) only redness values were affected by storage time. Parameter a* is influenced by the fat content (Andrés et al 2006).…”
Section: Colour Texture and Sensory Evaluationmentioning
confidence: 99%
“…Soyer and Ertaş (2007) showed that the oxidation degree in sucuk samples affected by storage time and fat content. Bozkurt and Erkmen (2007) concluded that the TBARS values affected by the fat content and ripening period.…”
Section: Resultsmentioning
confidence: 99%